SELF-AGGRESSION IN DELINQUENT TEENAGERS - VANCU, Gabriela Sorina; LAZĂR, Mioara Maria (International Journal of Legal and Social Order, 2022)
This paper aims to to approach the issue of self-aggression among juvenile delinquents due to the actuality of the phenomenon, the life risk, but also the social and mental health implications of their reintegration into society. Our study aimed to provide an overview of accentuated personality traits and relevant aspects of the psychological history of 40 young delinquents who are institutionalized, some of whom have a psychiatric history. We also observed the correlation of these traits with autolytic acts and illicit acts. The motivation of the study comes from the need to know adolescents who exhibit self-aggressive acts in order to intervene with programs to prevent suicide and juvenile delinquency.